Learning Harmony In Diversity: Tepa Slira And Empan Papan as a Mirror of Tolerance: Belajar Harmoni dalam Keberagaman: Tepa Slira dan Empan Papan sebagai Cermin Toleransi - Dian Rusydianti (Program S3 Pendidikan Islam Institut Pesantren KH. Abdul Chalim Pacet Mojokerto, 2025)
This study explores the significance of local culinary traditions, particularly Tepa Slira and Empan Papan, as a reflection of tolerance in diverse communities in Kudus, Indonesia. This research highlights how this culinary practice contains the value of mutual respect and understanding, which is essential for creating harmony in a multicultural society. Using a qualitative approach, this research involved in-depth interviews with community leaders, religious leaders, and culinary actors to gather insights into the role of these traditions in promoting social cohesion. Key findings suggest that Tepa Slira, which emphasizes mutual respect, and Empan Papan, which advocates for putting everything in its place, serve as cultural cornerstones for tolerance. This research reveals that these traditions not only strengthen social bonds during religious celebrations and cultural festivals but also provide a framework for dialogue and understanding between different faiths. Despite the challenges faced by globalization and social change, this study emphasizes the importance of educational initiatives and community involvement in preserving these values. Finally, these findings suggest that Kudus can be a model for other regions in building tolerant and harmonious societies through the celebration of diversity.